Análisis del clima organizacional de la empresa florícola XY del sector de Tabacundo año 2023 - Sánchez Guachamin, Martha María (2025)
Needing to improve the organizational climate of the Floricultural Company XY in Tabacundo, this research aimed to identify the factors affecting the organizational climate of employees working at the Floricultural Company "XY" located in Tabacundo Sector during the year 2023. A qualitative-quantitative approach was used, with a non-experimental design and descriptive scope. The information was collected by applying a survey utilizing the instrument by Koys and DeCottis (1991), which includes 8 structured dimensions: autonomy, cohesion, trust, pressure, support, recognition, equity, and innovation. The questionnaire had 23 questions related to the organizational climate, using the Likert scale as follows: 1= Never, 2= Almost-Never, 3= Sometimes, 4= Almost Always, and 5= Always. The survey was administered to the total population of the company, which covered 100 employees. The reliability of the instrument was validated through Cronbach's Alpha index, yielding a reliability score of 0.91. The research results led to the conclusion that, among the 8 dimensions applied in the survey, Autonomy and Pressure are acceptable for the work team, while the remaining 6 dimensions need improvement, through motivation, leadership, communication, job recognition, campaigns, and training, among others.